Contrasting Effects of Pharmacological, Procedural, and Surgical Interventions on Proportionate and Disproportionate Functional Mitral Regurgitation in Chronic Heart Failure. Issue 9 (27th August 2019) - Packer, Milton; Grayburn, Paul A.
Abstract : Two distinct pathways can lead to functional mitral regurgitation (MR) in patients with chronic heart failure and a reduced ejection fraction. When remodeling and enlargement of the left ventricle (LV) cause annular dilatation and tethering of the mitral valve leaflets, there is a linear relationship between LV end-diastolic volume and the effective regurgitant orifice area of the mitral valve. These patients, designated as having proportionate MR, respond favorably to treatments that lead to reversal of LV remodeling and a decrease in LV volumes (eg, neurohormonal antagonists and LV assist devices), but they may not benefit from interventions that are directed only at the mitral valve leaflets (eg, transcatheter mitral valve repair). In contrast, when ventricular dyssynchrony causes functional MR attributable to unequal contraction of the papillary muscles, the magnitude of regurgitation is greater than that predicted by LV volumes. These patients, designated as having severe but disproportionate MR, respond favorably to treatments that are directed to the mitral valve leaflets or their supporting structures (eg, cardiac resynchronization or transcatheter mitral valve repair), but they may derive little benefit from interventions that act only to reduce LV cavity size (eg, pharmacological treatments). This novel conceptual framework reflects the important interplay between LV geometry and mitral valve function in determining the clinical presentation of patients, and it allows characterization of the determinants of functional MR to guide the most appropriate therapy in the clinical setting.